2009
DOI: 10.1200/jco.2009.27.18_suppl.cra4030
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of primary tumor in patients with synchronous stage IV colorectal cancer receiving combination chemotherapy without surgery as initial treatment

Abstract: A B S T R A C T PurposeThe purpose of this study was to describe the frequency of interventions necessary to palliate the intact primary tumor in patients who present with synchronous, stage IV colorectal cancer (CRC) and who receive up-front modern combination chemotherapy without prophylactic surgery. Patients and MethodsBy using a prospective institutional database, we identified 233 consecutive patients from 2000 through 2006 with synchronous metastatic CRC and an unresected primary tumor who received oxal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
1
17

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(95 citation statements)
references
References 2 publications
3
74
1
17
Order By: Relevance
“…Overall Survival, Progression-Free Survival and Response Rate [ Table 1] Table 1 gives an overview of data on overall survival (OS), progression-free survival (PFS) and response rate (RR) reported by 7 randomized controlled trials M A N U S C R I P T (RCTs) 19-25,31 , 4 prospective 8,26-28 and 3 retrospective studies 11,29,30 . A recent Cochrane Database systematic review by Wagner et al, including 5 randomized trials (>3000 patients) 19,22,23,25,31 , concluded BV prolongs both PFS and OS in patients with mCRC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall Survival, Progression-Free Survival and Response Rate [ Table 1] Table 1 gives an overview of data on overall survival (OS), progression-free survival (PFS) and response rate (RR) reported by 7 randomized controlled trials M A N U S C R I P T (RCTs) 19-25,31 , 4 prospective 8,26-28 and 3 retrospective studies 11,29,30 . A recent Cochrane Database systematic review by Wagner et al, including 5 randomized trials (>3000 patients) 19,22,23,25,31 , concluded BV prolongs both PFS and OS in patients with mCRC.…”
Section: Resultsmentioning
confidence: 99%
“…Two patients with primary tumor complications (<1%) died within 30 days of surgery. The authors didn't specify whether these patients were on BV-treatment, but they concluded that the risk of emergent intervention was not associated with the use of BV 30 . Of 529 patients under BV-based treatment in the ECOG study E3200 only 1 developed a grade 4 bleeding that required a hemostatic intervention and 6 events of bowel perforation were reported, 2 of which needed surgery and 2 cases were fatal 22 .…”
Section: Risk For Emergency Surgery Under Bv-treatment?mentioning
confidence: 99%
“…Models of simultaneous colon and liver resection as well as resection of the primary followed by chemotherapy to stabilise the liver tumours with the intent to proceed to staged hepatectomy are being debated [26]. Studies have shown a survival benefi t to neoadjuvant chemotherapy and resection of liver metastases prior to the resection of the colon primary [26][27][28].…”
Section: Management Of Colorectal Primary For Stage IV Diseasementioning
confidence: 99%
“…Poultsides et al retrospectively reviewed prospective data on 233 patients over a 6-year period with synchronous metastatic CRC and an unresected primary who received neoadjuvant chemotherapy [27]. Of this group, 93% never required any surgical intervention for palliation of the primary.…”
Section: Management Of Colorectal Primary For Stage IV Diseasementioning
confidence: 99%
See 1 more Smart Citation